1980
DOI: 10.2307/3114215
|View full text |Cite
|
Sign up to set email alerts
|

Business Demand and the Development of the Telegraph in the United States, 1844–1860

Abstract: “The telegraph system in America is eminently characteristic of the national mind. At its very birth, it became the handmaiden of commerce.” So wrote the editor of a telegraph trade journal in 1853. Professor Du Boff describes an antebellum American business community that was as ready for a “revolution” in its size and structure as the dawning science of electricity was ready to make it happen. The result was the telegraph and its enthusiastic adoption in a few short years by a business system that quickly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 6 publications
1
13
0
2
Order By: Relevance
“…El impacto de las TIC en la productividad de los países desarrollados ha sido ampliamente analizado en la literatura existente (Crafts 2010;DuBoff 1980;Madden y Savage 1998;Van Ark et al 2008). Como se ha señalado, desde mediados de la década de 1990, Estados Unidos se benefició de un aumento sin precedentes de la productividad como resultado de la mayor eficiencia de los sectores de las TIC.…”
Section: Implementación De Las Tic En América Latinaunclassified
“…El impacto de las TIC en la productividad de los países desarrollados ha sido ampliamente analizado en la literatura existente (Crafts 2010;DuBoff 1980;Madden y Savage 1998;Van Ark et al 2008). Como se ha señalado, desde mediados de la década de 1990, Estados Unidos se benefició de un aumento sin precedentes de la productividad como resultado de la mayor eficiencia de los sectores de las TIC.…”
Section: Implementación De Las Tic En América Latinaunclassified
“…In a cross-sectional model including 75 developed and developing countries, Kiiski and Pohjola report values for the speed of diffusion that range from 0.186 to 0.527. 5 The present paper finds that the speed of diffusion can vary from 0.269 to 0.375 for Internet hosts, from 0.509 to 0.656 for Internet users, and from 0.529 to 0.579 for personal computers. However, given that the RHS variables are not the same, it is difficult to make a more meaningful comparison of the results derived in the two studies.…”
Section: Determinants Of Ictmentioning
confidence: 99%
“…The evidence about changes in markets and communities in developing countries is ambiguous. While there are examples of significant benefits from the use of ICT on credit and trade markets in some countries [2,33], there are studies that highlight the limited extent of the impact of these technologies [1,5].…”
Section: Description Of the Data And Methodologymentioning
confidence: 99%
“…Telecommunications, as a mechanism for reducing information asymmetry, are argued to be a major determinant of market development and economic growth, and empirical research has confirmed this relationship (Garbade & Silber, 1978;DuBoff, 1980;Hardy, 1980;Nathaniel, 1984;Norton, 1992). However, other factors, many of which are institutionally determined, should be present if investment in telecommunications is to lead to growth.…”
Section: Introductionmentioning
confidence: 85%